![image](https://tex.z-dn.net/?f=3%29+log_%7B3%7D%28+x%5E%7B2%7D+-2x-2%29+%5Cleq+0%2C+%5C%5C+%0A+%5Cleft+%5C%7B+%7B%7B+x%5E%7B2%7D+-2x-2%3E0%2C%7D+%5Catop+%7B+x%5E%7B2%7D+-2x-2+%5Cleq+1%3B%7D%7D+%5Cright.++%5Cleft+%5C%7B+%7B%7B+x%5E%7B2%7D+-2x-2%3E0%2C%7D+%5Catop+%7B+x%5E%7B2%7D+-2x-3+%5Cleq+0%3B%7D%7D+%5Cright.+%5C%5C+x%5E%7B2%7D+-2x-2%3D0%2C+%5C%5C+D%3D1%5E2%2B2%3D3%2C+%5C%5C+x_1%3D1-%5Csqrt%7B3%7D%2Cx_2%3D1%2B+%5Csqrt%7B3%7D%2C+%5C%5C+x%5E%7B2%7D+-2x-3%3D0%2C+%5C%5C+x_1%3D-1%2Cx_2%3D3%3B+%5C%5C+%5Cleft+%5C%7B+%7B%7B%28x-1%2B%5Csqrt%7B3%7D%29%28x-1-%5Csqrt%7B3%7D%29%3E0%2C%7D+%5Catop+%7B+%28x%2B1%29%28x-3%29+%5Cleq+0%3B%7D%7D+%5Cright.++%5Cleft+%5C%7B+%7B%7B+%5Cleft+%5B+%7B%7Bx%3C1-%5Csqrt%7B3%7D%2C%7D+%5Catop+%7Bx%3E1%2B%5Csqrt%7B3%7D%2C%7D%7D+%5Cright.+%7D+%5Catop+%7B+-1+%5Cleq+x+%5Cleq+3%3B%7D%7D+%5Cright.++)
0,} \atop { x^{2} -2x-2 \leq 1;}} \right. \left \{ {{ x^{2} -2x-2>0,} \atop { x^{2} -2x-3 \leq 0;}} \right. \\ x^{2} -2x-2=0, \\ D=1^2+2=3, \\ x_1=1-\sqrt{3},x_2=1+ \sqrt{3}, \\ x^{2} -2x-3=0, \\ x_1=-1,x_2=3; \\ \left \{ {{(x-1+\sqrt{3})(x-1-\sqrt{3})>0,} \atop { (x+1)(x-3) \leq 0;}} \right. \left \{ {{ \left [ {{x<1-\sqrt{3},} \atop {x>1+\sqrt{3},}} \right. } \atop { -1 \leq x \leq 3;}} \right. " alt="3) log_{3}( x^{2} -2x-2) \leq 0, \\
\left \{ {{ x^{2} -2x-2>0,} \atop { x^{2} -2x-2 \leq 1;}} \right. \left \{ {{ x^{2} -2x-2>0,} \atop { x^{2} -2x-3 \leq 0;}} \right. \\ x^{2} -2x-2=0, \\ D=1^2+2=3, \\ x_1=1-\sqrt{3},x_2=1+ \sqrt{3}, \\ x^{2} -2x-3=0, \\ x_1=-1,x_2=3; \\ \left \{ {{(x-1+\sqrt{3})(x-1-\sqrt{3})>0,} \atop { (x+1)(x-3) \leq 0;}} \right. \left \{ {{ \left [ {{x<1-\sqrt{3},} \atop {x>1+\sqrt{3},}} \right. } \atop { -1 \leq x \leq 3;}} \right. " align="absmiddle" class="latex-formula">